POLITICAL BEHAVIOR AND ATTITUDES IN EMERGING DEMOCRACIES (International Journal of Food and Nutritional Sciences, 2022)
The aim of this study is to examine the Political Behavior and Attitudes in EmergingDemocracies. Political behavior and attitudes in emerging democracies are vital forunderstanding the prospects of democratic consolidation and stability. These democracies,transitioning from authoritarian regimes to democratic governance, encounter distinctchallenges that shape their political landscape, including historical autocratic legacies,economic instability, social divisions, and the effort to build robust democratic institutions.Political participation in emerging democracies takes various forms, from voting in electionsto engaging in protests and activism. Initially, voter turnout is often high due to the noveltyand optimism surrounding the democratic transition. However, this enthusiasm may diminishas citizens become disillusioned with slow reforms and persistent corruption.